2008
DOI: 10.1590/s0100-40422008000800030
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do intemperismo artificial em quatro madeiras tropicais monitorado por espectroscopia de infravermelho (DRIFT)

Abstract: Recebido em 26/3/08; aceito em 12/6/08; publicado na web em 10/11/08 EFFECT oF aRTIFICIaL wEaThERINg oN TRoPICaL wooDS moNIToRED By INFRaRED SPECTRoSCoPy (DRIFT). Four tropical woods, were investigated to compare their performance and natural resistances to artificial weathering using the diffuse reflectance infrared Fourier transform spectroscopy (DRIFT). The species were garapeira (Apuleia leiocarpa), itaúba (Mezilaurus itauba) and tauari (Couratari sp.), woods traditionally indicated for exterior uses, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
9
0
7
Order By: Relevance
“…Conjuntamente, son identificados otros inconvenientes como la disminución del rendimiento de los productos aplicados a la superficie de la madera (Pastore et al 2008), productos tales como adhesivos y recubrimientos.…”
Section: Introductionunclassified
“…Conjuntamente, son identificados otros inconvenientes como la disminución del rendimiento de los productos aplicados a la superficie de la madera (Pastore et al 2008), productos tales como adhesivos y recubrimientos.…”
Section: Introductionunclassified
“…Aldehydes showed a strong band of carbonyl group (CO) in the range between 1740 and 1725 cm −1 . This band can be attributed to both carbonyl groups of aldehyde functions and unconjugated ketone of the lignins and holocelluloses, as may have been due to the use of glurataldehyde such as a crosslink agent in the final step of the modification . For the three modified materials (TP, PAPA, PAAP) was observed that this band was intensified in comparison to the alkaline material.…”
Section: Resultsmentioning
confidence: 99%
“…Spectra of wood are very similar and the assignments of the main bands are well established and described in literature. 30 The spectra of the carbon product shows the following main features: (A) Initially, the intensity of the band around 3400 cm -1 due to the vibrational mode of OH stretching bond in the wood is relatively higher than in charcoal, which suggests loss of the constitution water that is impregnated in the cell wall of wood with an increasing of the temperature. (B) The decomposition of lignin is evident by the reduction of C = C vibrational bands of aromatic rings, in ca.…”
Section: Analysis In the Medium Infraredmentioning
confidence: 99%
“…(C) The non conjugated bonds C=O in 1734 cm -1 assigned to hemicelluloses decreased markedly in intensity. 30 (D) A formation of an aromatic network with the appearance of three bands at low frequencies 880, 820 and 757 cm -1…”
Section: Analysis In the Medium Infraredmentioning
confidence: 99%